Solubility and chemical interaction of nitrocellulose in plasticisers - Flood, Nathan; Parker, Matthew (Cranfield University, 2016)
Technical paper presented at the 2016 Defence and Doctoral Symposium. Abstract: Nitrocellulose (NC) is commonly used as an energetic binder in explosive and propellant formulations. During the formulation and casting stages NC can be mixed with a variety of plasticisers with the aim of tuning the mechanical properties of the charge to suit the specified requirements. Historically there have been issues with the solubility of NC in various plasticisers which has created manufacturing problems leading to failures of missiles.The research presented from two programmes of work funded by the WSTC, Propellant Bonding and Nitrocellulose: Degrees of Freedom, has investigated how NC interacts with three plasticisers; Triacetin (TA), Diallyl Phthalate (DAP) and Nitroglycerine (NG). The solubility was investigated using time-lapse microscopy and the chemical interaction was investigated using Attenuated Total Reflectance Infrared Spectroscopy (ATR-FT-IR) and compared with the five modes describing the swelling and dissolution mechanisms of wood and cellulose fibres.The mechanisms observed for nitrocellulose follow the dissolution modes described for wood and cotton fibres. It was found that TA had the highest solubility with respect to NC whilst NG had the lowest; variation in the swelling and gelation of NC has been rationalised by the crystallinity within the sample. Changes in the cellulosic fibrillar substructure of NC due to nitration and processing results in changes in its crystallinity. This variation of crystallinity subsequently affects the chemical interactions of solvent and plasticiser molecules with NC and the bulk movement of these molecules through the material. ATR-FT-IR demonstrates the presence of constructive bonding interactions between NC and TA or DAP, which manifests as swelling and gelation at the bulk-level. NG exhibits no apparent molecular bonding by IR measurement, and sorption only into the NC fibre, without the extensive swelling and gelation observed in the other regimes.
Keywords: 'DSDS16 technical paper'; 'Organic Chemistry not elsewhere classified'